Clinico-anatomical correlations in asphyxiated babies who developed spastic quadriparesis at one year of age (Bangladesh Journal of Medical Science, 2016)
Abstrcat not availableBangladesh Journal of Medical Science Vol.15(2) 2016 p.289-291